PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN PADA PT. CAHAYA PELITA ANDHIKA - Siti Aijah; Nur Ainun Hasibuan; Hadijah Sipahutar (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2022)
Financial performance is a description of the temptation or success of the company's program implementation in realizing the company's vision and mission. This study aims to examine the effect of performance on the company's financial value at PT. Andhika's lamp. This study used three stages of data analysis, namely descriptive statistical analysis, classical assumption test, and multiple linear regression analysis with a significance level of 5%. The results of this study prove that the variables of liquidity and profitability have a significant effect on firm value. While the solvency variable has no significant effect on firm value.